Integrated Islamic Social Instrument for Sustainable Development: Case of SDG-14 - Rusydiana, Aam Slamet; Sukmana, Raditya; Laila, Nisful (SMART Insight, 2023)
The fourteenth SDG objective summarizes discussions on waste and pollution management, marine ecosystems, limiting storm damage, and protecting marine health as part of efforts to reduce and adapt to climate change. Waqf, on the other hand, is an instrument of Islamic social finances that has a sustainable character and is relevant to the Sustainable Development Goals, therefore it can be used to safeguard the environment, particularly undersea ecosystems. This study aims to identify the waqf model that is relevant to the SDGs by prioritizing the waqf model that may be adopted in Indonesia, which is in line with SDGs 14 from a Maqashid Syariah perspective. The results indicate that the Sukuk waqf model is the appropriate capital to assist the defense of the fourteen Sustainable Development Goals, namely the protection of the undersea ecology. This research also presents an appropriate blue Sukuk waqf model framework.